Influence of land cover types on soil quality and carbon storage in Moramo Education Estate, Southeast Sulawesi, Indonesia - SYAMSU ALAM; SAHTA GINTING; M. TUFAILA HEMON; SITTI LEOMO; LAODE MUHAMMAD HARJONI KILOWASID; JUFRI KARIM KARIM; YUSANTO NUGROHO; JERIELS MATATULA; PANDU YUDHA ADI PUTRA WIRABUANA (Society for Indonesian Biodiversity, 2022)
Abstract. Alam S, Ginting S, Hemon MT, Leomo S, Kilowasid LMH, Karim J, Nugroho Y, Matatula J, Wirabuana PYAP. 2022. Influence of land cover types on soil quality and carbon storage in Moramo Education Estate, Southeast Sulawesi, Indonesia. Biodiversitas 23: 4371-4376. This study investigated the influence of different land cover types on soil quality and carbon storage in Moramo Education Estate (MEE). Information is required as fundamental consideration to determine the best landscape management strategies for supporting soil conservation and climate change mitigation. Data were collected from three types of land cover generally found in this area, including forests, shrubs, and savannas. Three permanent sampling plots were randomly placed in every land cover as replicates with a size of 20 m × 20 m. Six parameters were used to describe the soil quality, i.e., soil acidity, soil organic carbon, total nitrogen, available phosphorus, exchangeable potassium, and cation exchange capacity. The above and belowground carbon storage from every plot was quantified. The soil quality and carbon storage among land cover types were compared using analysis of variance and Tukey’s honestly significant difference. Pearson’s correlation analysis was also applied to evaluate the relationship between soil quality and carbon storage. The results show that soil quality significantly differed in the exchangeable potassium and cation exchange capacity. A similar trend was also demonstrated in aboveground carbon storage. The highest average carbon storage was recorded in forests (150.50 ± 27.79 t ha?1), followed by shrubs (52.50 ± 15.02 t ha?1) and savannas (45.97 ± 4.42 t ha?1). The total carbon storage at different land covers was significantly correlated to soil acidity, available phosphorus, and cation exchange capacity. Carbon storage improved with the increased available phosphorus and cation exchange capacity. In contrast, carbon storage was negatively correlated with soil acidity. Overall, the land cover types significantly influenced soil quality and carbon storage in MEE.